PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PENGENDALIAN PIUTANG PADA PT BAROKAH ADI SEJAHTERA MEDAN - Hari Cahyo; Henny Tri Astuti Kurnia Ningsih; Farida Khairani Lubis (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
PT. Barokah Adi Sejahtera Medan is a company engaged in cargo and shipping services. In carrying out its business, the sales accounting information system and internal control must be implemented properly so that receivables can be minimized effectively. The operational activities and transactions that occur daily look diverse. In an effort to increase sales of the company, the need to control receivables that have an important role to sell in order for the sales to occur in accordance with procedures and able to generate maximum profitability for the company. The research concluded that accounting information systems have a positive and significant effect on receivables control as the results of the study based on the t test that t-count is greater than the t-table of 2.94 2.02. Internal Control has a positive and significant effect on receivable control as the results of the study based on the t-test that the t-count is greater than the t-table of 2.92 2.02. Simultaneously or jointly Accounting Information System (X1) and Internal Control (X2) affect receivable control (Y) as the calculation of simultaneous tests i.e. F-count is greater than f-table or 8,285 4.08. The magnitude of the influence of variable X1, X2 on[ variable Y based on determinant test is 55.60%